Scrotal lymphangioma in an infant: A compelling case study of comprehensive diagnosis and management - Qiu Yan Duan; Yang Feng Lou; Long Fei Yang; Peng Zhou (Urology Case Reports)
We report a rare case of scrotal lymphangioma in a 6-year-old boy, highlighting its role in the differential diagnosis of pediatric scrotal swelling. This benign vascular lesion's etiology, pathophysiology, clinical features, diagnostic approaches, treatment options, and prognosis are discussed. Our case underscores the importance of awareness and comprehensive management for early diagnosis and effective treatment, aiming to enhance outcomes in this uncommon pediatric condition and provide insights for healthcare professionals.